2020
DOI: 10.1002/hed.26456
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab‐related tracheobronchial chondritis: Extremely rare manifestation of an immune‐related adverse effect

Abstract: Background: Programmed death-1 checkpoint inhibitors, such as nivolumab, have successfully been utilized for recurrent or metastatic squamous cell carcinoma of the head and neck; however, their use may be associated with immune-related adverse effects (irAEs). Methods : We describe a case of tracheobronchial chondritis as a rare irAE in a 72-year-old man with multiple pulmonary metastases of hypopharyngeal squamous cell carcinoma treated with nivolumab, who was seen with a 2-week history of fever, nonproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In contrast, the management of side effects, such as radiation-induced lung injury and immune-related adverse events, has also become increasingly complicated. Few studies have reported that radiotherapy or ICIs may be implicated in the development or worsening of RP ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the management of side effects, such as radiation-induced lung injury and immune-related adverse events, has also become increasingly complicated. Few studies have reported that radiotherapy or ICIs may be implicated in the development or worsening of RP ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first case of pembrolizumab-induced RP with isolated auricular lesions. A PubMed search for English articles describing the clinical characteristics of ICI-induced chondritis published until March 2023 yielded only five cases treated with nivolumab, another anti-PD-1 antibody ( Table 1 ) (3) , (4) , (5) , (6) , (7) . As shown in Table 1 , all patients belonging to 49-72 years age group had 50% of having hypopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…All reported cases, excluding the present case wherein the affected cartilage was auricular, mainly included isolated tracheobronchial chondritis. Discontinuing ICIs with varied immunosuppressants improved the symptoms (3) , (5) , (6) . Notably, all previous cases were from Japan, suggesting that genetic factors could be associated with chondritis development and human leukocyte antigen (HLA).…”
Section: Discussionmentioning
confidence: 99%
“…ICIs for advanced cancers are known to cause immune‐related adverse events (AEs) including rheumatic diseases (1). Tracheal cartilage lesions resulting from an immune‐related AE are rare; however, tracheobronchial chondritis could be an initial manifestation of an immune‐related AE (2,3). Physicians should be aware that ICI treatment can cause tracheobronchial chondritis, which can be a fatal immune‐related AE.…”
mentioning
confidence: 99%